BANKING SYSTEM OF TURKESTAN IN THE PERIOD FROM THE END OF XIX TO THE BEGINNING OF XX CENTURY: HISTORICAL ANALYSIS, KEY STAGES AND FACTORS OF DEVELOPMENT - Parvina Ismoilova (Western European Studies, 2024)
This research is devoted to the study of historical development of banking practice in Turkestan at the turn of the 19th and 20th centuries. It traces the process of formation and evolution of the banking sector in the region, from the emergence of the first modern banks to the introduction of innovative financial instruments. Special attention is paid to the impact of banking on the economy and social stability of the region.
Keywords: Turkestan; factors; banking activity; developing